2011
DOI: 10.1137/100799265
|View full text |Cite
|
Sign up to set email alerts
|

Restarting the Nonsymmetric Lanczos Algorithm for Eigenvalues and Linear Equations Including Multiple Right-Hand Sides

Abstract: A restarted nonsymmetric Lanczos algorithm is given for computing eigenvalues and both right and left eigenvectors. The restarting limits the storage so that finding eigenvectors is practical. Restarting also makes it possible to deal with roundoff error in new ways. We give a scheme for avoiding near-breakdown and discuss maintaining biorthogonality. A system of linear equations can be solved simultaneously with the eigenvalue computations. Deflation from the presence of the eigenvectors allows the linear equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Whenever the matrix changes in the sequence, we call RBiCG to perform the linear solve. This helps to approximate both left and right invariant subspaces, which are not easily available from the RBiCGSTAB iterations (sometimes a left invariant subspace is available from a right invariant subspace [2,24]). The primary system right-hand side comes from the PDE.…”
Section: Parametric Model Order Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whenever the matrix changes in the sequence, we call RBiCG to perform the linear solve. This helps to approximate both left and right invariant subspaces, which are not easily available from the RBiCGSTAB iterations (sometimes a left invariant subspace is available from a right invariant subspace [2,24]). The primary system right-hand side comes from the PDE.…”
Section: Parametric Model Order Reductionmentioning
confidence: 99%
“…This corresponds to linear systems where only the right-hand sides change. This is an effective strategy because it has been shown that the recycle space can be useful for multiple consecutive systems [25,21,24,1]. Moreover, using RBiCG for all systems will be expensive since an unnecessary dual system would be solved at each step in the sequence.…”
Section: Parametric Model Order Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, without the locally optimal restarting technique, its spectral approximations are not accurate eigenvectors and therefore have been used mainly in applications where the matrix changes between right‐hand sides. On the other hand, the deflated nonsymmetric Lanczos in is a thick restarted eigensolver. For deflation, other methods project the obtained eigenvectors at every step ( GMRes , Recycled BiCG ) or at every restart ( GMRes‐Proj ).…”
Section: Introductionmentioning
confidence: 99%
“…Block methods are a popular way to solve systems with multiple right-hand sides (see for example [1][2][3][4][5]). Another approach is deflating eigenvalues (e.g., [6][7][8][9][10][11]). However, we will concentrate on a third approach, the seed conjugate gradient (CG) method [12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%